STRATEGI PENURUNAN KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS GAJAH MADA TEMBILAHAN - Tri Utami; Sukendi; Agrina (EcoNews, 2020)
Dengue Hemorrhagic Fever (DHF) is a contagious disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito. There were 144 dengue cases, without any deaths in 2016, while in 2017 it decreased to 54 cases, without any deaths in Indragiri Hilir Regency. Therefore, it was necessary to carry out a strategy to solve the problem. This research aims to analyze the strategy to reduce the case of dengue hemorrhagic fever in Puskesmas Gajah Mada, Tembilahan. The method in the research was interviews, observation and test. To data analysis, the researcher used SWOT analysis. The results showed that UPT Puskesmas Gajah Mada implemented essential health programs and programs development. For making the program will be success, it requires good human resources that supported by good management. Good management always concern to the completeness and accuracy of the data which is basic data and other supporting data that collected in the Puskesmas Profile. Puskesmas management is connecting structure that worked systematically to produce the effective and efficient Puskesmas outputs. The connecting structure of activities include Planning, Movement, Implementation, Supervision, Control, and Assessment which cannot be separated from the accuracy of the data, which is basic data and supporting data.